Validation of a solar powered blood pressure device, suitable for use in low resource settings. (7th June 2011) - de Greef, A; Ashraf, D; Saad, L; Hezelgrave, N L; Shennan, A H
Abstract : Hypertensive diseases in pregnancy are a significant cause of morbidity and mortality, particularly in low resource settings (LRS). Pre-eclampsia and eclampsia alone claim up to 50 000 women's lives globally each year, with an estimated fetal case death of 7–25% in African countries.1 Accurate and regular antenatal blood pressure (BP) monitoring is a cost effective means for early identification and management of hypertensive disease in pregnancy. No BP devices suitable for use in LRS have been assessed for accuracy in pregnancy. Aim: To evaluate the accuracy of the semi-automatic Omron HEM-Solar BP device in pregnancy and pre-eclampsia according to the British Hypertension Society (BHS) protocol. Methods: Pregnant women were recruited from St Thomas' Hospital (UK) and Kimberley Hospital Complex (South Africa). Trained observers took nine sequential same-arm BP measurements from each woman, alternating between mercury sphygmomanometry and the device. Data were analysed according to BHS guidelines, requiring an A or B grade (for both systolic and diastolic pressures) to pass. Results: The device achieved an A/B grade in pregnancy (n=30) including five women with pre-eclampsia. The mean difference (SD) between observers and device was −4.0(5.8) mm Hg and −0.1(8.5) mm Hg for SBP and DBP respectively. Conclusion: The Omron HEM-Solar can be recommended for clinical use in pregnancy. Low cost, ease of use and solar power make it ideally suited to a LRS for use by skilled and unskilled health workers. It has the potential to facilitate early diagnosis of pre-eclampsia and address the disproportionate burden of maternal and infant morbidity in LRS.